Education and Consumer Informatics: Improvements in Existing Systems - Boyer, C.; Managing Editor for the IMIA Yearbook Section on Education and Consumer Informatics (Yearbook of Medical Informatics, 2008)
Objectives To provide an overview of the current excellent research done in the field of advancements in Education and Consumer Informatics as well as studies done to better understand, the already existing systems.Method Synopsis of the articles on education and consumer health selected for the IMIA Yearbook of Medical Informatics 2008.Results In the domain of education, eHealth literacy becomes a key topic and a challenge, the Internet evolving as the primary medium to access health information. A system developed to measure the eHealth literacy level of consumers reflects the importance of this skill. In consumer health informatics, the selected papers emphasize valuable advances in bridging the information gap as well as the growing implementation of functioning systems.Conclusion The selected articles highlight the need for recognising existing weak links in the healthcare system and then strengthening them through patient education and involvement, as well as possible improvements through real-world implementations.
Keywords: Education; consumer health informatics; health literacy; tele-consultation; Internet usage study